"I Don't Know Why I've Got this Pain!" Allostasis as a Possible Explanatory Model. Issue 5 (23rd February 2022) - Rabey, Martin; Moloney, Niamh
Abstract: : Explaining the onset and maintenance of pain can be challenging in many clinical presentations. Allostasis encompasses the mechanisms through which humans adapt to stressors to maintain physiological stability. Due to related neuro-endocrine-immune system effects, allostasis and allostatic load (the cumulative effects on the brain and body that develop through the maintenance of physiological stability) offer the potential to explain the development and maintenance of musculoskeletal pain in certain cases. This paper outlines the concept of allostatic load, highlights the evidence for allostatic load in musculoskeletal pain conditions to date, and discusses mechanisms through which allostatic load influences pain, with particular focus on hypothalamic–pituitary–adrenal axis and sympathetic nervous system function and central, brain-driven governance of these systems. Finally, through case examples, consideration is given as to how allostatic load can be integrated into clinical reasoning and how it can be used to help explain pain to individuals and guide clinical decision-making. Impact: Awareness of the concept of allostatic load, and subsequent assessment of physical and psychological stressors potentially contributing to allostatic load, may facilitate a broader understanding of the multidimensional presentations of many people with pain, both acute and persistent. This may facilitate discussion between clinicians and their patients regarding broader influences on their presentations and drive more targeted and inclusive pain management strategies.